2019
DOI: 10.35683/jcm19041.0029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change and extreme weather conditions on wine growing within the Stellenbosch region

Abstract: The main wine producing region of South Africa is particularly vulnerable to the impact of extreme weather events and climate change. Any shift in weather patterns impacts on grape quality and poses challenges for the process of turning grapes into wine, and may ultimately impact on the final quality of the wine that is produced. This article explores the impact of extreme weather conditions and ultimately climate change on wine growing regions in South Africa and suggests ways of managing such change. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Increased warming with associated increased evapotranspiration and increased frequency and intensity of extreme events such as droughts, wildfires floods, and heatwaves [142] will bring increased pressure for irrigation and less reliance on precipitation, more so for old world producers than new world producers [92]. For South Africa, this situation is especially dire because the country is one of the most water-scarce countries in the world, with large areas classified as arid or semi-arid [27].…”
Section: Environmental Sustainability In Climate Change Of Grape and mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased warming with associated increased evapotranspiration and increased frequency and intensity of extreme events such as droughts, wildfires floods, and heatwaves [142] will bring increased pressure for irrigation and less reliance on precipitation, more so for old world producers than new world producers [92]. For South Africa, this situation is especially dire because the country is one of the most water-scarce countries in the world, with large areas classified as arid or semi-arid [27].…”
Section: Environmental Sustainability In Climate Change Of Grape and mentioning
confidence: 99%
“…Considerable research has been conducted on the three individual pillars of sustainability and in the context of climate change in the South African grape and wine industry [25][26][27][28][29][30]. However, a major gap in these studies is the provision of a holistic overview of the three pillars in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the wine industry is one of the most actively researched areas in relation to climate change, taking into account the related sustainability challenges and opportunities in many different scientific and geographical areas [12][13][14][15]. Numerous studies can be found that consider viticulture and climate change-related issues from Europe [16][17][18][19][20], North-and South-America [21][22][23][24], South-Africa [25][26][27], and Australia [28][29][30].…”
Section: Introductionmentioning
confidence: 99%